2019
DOI: 10.1186/s12909-019-1697-5
|View full text |Cite
|
Sign up to set email alerts
|

Medical faculty members’ perception of smartphones as an educational tool

Abstract: Background The rapid adoption of modern technology has changed many aspects of our life and communication; it has the power to influence and change the way we teach, learn and practice different types of professions mainly teaching and health care providing. Smartphone applications are increasingly becoming popular and widespread. Generally, these applications are likely to play a significant role in supporting education, in general, and medical education, in particular. This study aims at investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…Notably in this study, bedside teaching via WeChat did not achieve the expected outcome although the application of WeChat in medical education at several medical colleges in China has demonstrated satisfying outcomes in both problem-based learning and students-centered teaching (Wang et al, 2017;Zeng et al, 2016b;Sun et al, 2016;Zeng et al, 2016a). All these studies are in accordance with another recent research showing that smartphones could be a significant learning tool for students as well as an addition instrument to academic teaching practice for staff (Jabali et al, 2019). However, these previous studies usually applied WeChat among junior medical students or residents.…”
Section: The Preference Of Participants With the Three Bedside Teaching Methodssupporting
confidence: 86%
“…Notably in this study, bedside teaching via WeChat did not achieve the expected outcome although the application of WeChat in medical education at several medical colleges in China has demonstrated satisfying outcomes in both problem-based learning and students-centered teaching (Wang et al, 2017;Zeng et al, 2016b;Sun et al, 2016;Zeng et al, 2016a). All these studies are in accordance with another recent research showing that smartphones could be a significant learning tool for students as well as an addition instrument to academic teaching practice for staff (Jabali et al, 2019). However, these previous studies usually applied WeChat among junior medical students or residents.…”
Section: The Preference Of Participants With the Three Bedside Teaching Methodssupporting
confidence: 86%
“…Similarly, students with a negative attitude towards social media as a channel for academic learning found it as a source of distraction that also hampers their performance. In another study conducted on students of a healthcare institute, the authors found that attitude towards smartphone usage during lectures significantly influenced academic performance [12,56,89]. Various functions of a smartphone can enhance the learning process.…”
Section: Attitude As a Mediatormentioning
confidence: 99%
“…Its simplistic and straightforward design could allow the TSPA to be a useful tool in busy and complicated clinical environments. Smart phones continue to gain popularity as an educational tool among faculty members and students in the human medical profession 28 29. Veterinary institutions should consider incorporating these devices within their current curriculums, however, there is potential for them to be a source of distraction.…”
Section: Discussionmentioning
confidence: 99%